2014
DOI: 10.3390/toxins6020693
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxin: Chemistry, Toxicity, Source, Distribution and Detection

Abstract: Tetrodotoxin (TTX) is a naturally occurring toxin that has been responsible for human intoxications and fatalities. Its usual route of toxicity is via the ingestion of contaminated puffer fish which are a culinary delicacy, especially in Japan. TTX was believed to be confined to regions of South East Asia, but recent studies have demonstrated that the toxin has spread to regions in the Pacific and the Mediterranean. There is no known antidote to TTX which is a powerful sodium channel inhibitor. This review aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
286
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(324 citation statements)
references
References 213 publications
(676 reference statements)
4
286
2
3
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 8 These complications make most laboratory synthesis approaches for TTX and its analogs unfeasible for commercial scale-up (54) .…”
Section: Downloaded By [António Raposo] At 05:58 25 July 2015mentioning
confidence: 99%
See 2 more Smart Citations
“…A c c e p t e d M a n u s c r i p t 8 These complications make most laboratory synthesis approaches for TTX and its analogs unfeasible for commercial scale-up (54) .…”
Section: Downloaded By [António Raposo] At 05:58 25 July 2015mentioning
confidence: 99%
“…It is assumed that arginine is the precursor moiety for TTX production within the organism ( Figure 3) (53,55) . A likely biosynthetic route to TTX incorporates arginine and either a C5 branched sugar or an alkyl precursor (54) .…”
Section: Downloaded By [António Raposo] At 05:58 25 July 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…Uddin et al (2013) menyatakan bahwa jenis racun tetrodotoksin pada uji fitokimia terdeteksipada uji alkaloid. Tetrodotoksin akan aktif apabila adanya glikosida (karbohidrat), karena racun tersebut dapat disintesis bila terdapat kuinon atau karbohidrat (Bane et al 2014). Penelitian Uddin et al (2013) menunjukkan bahwa nilai uji fitokimia yang memiliki kandungan racun dari ikan buntal jenis Tetraodon cutcutia adalah hatinya, karena memiliki nilai positif pada uji alkaloid dan glikosida.…”
Section: Analisis Fitokimiaunclassified
“…For a long time, tetrodotoxin was considered a metabolic product of fishes [23], but studies have demonstrated that certain bacteria, such as Vibrio sp., produce the toxin and are incorporated into fishes through the food chain [23,24]. The toxin is then stored in some organs and used as a defense against predators [9,25].…”
Section: Poisonous Fishesmentioning
confidence: 99%